Effectiveness and toxicity of first-line methotrexate chemotherapy in low-risk postmolar gestational trophoblastic neoplasia: The New England Trophoblastic Disease Center experience - Maestá, Izildinha [UNESP]; Nitecki, Roni; Horowitz, Neil S.; Goldstein, Donald P.; de Freitas Segalla Moreira, Marjory [UNESP]; Elias, Kevin M.; Berkowitz, Ross S. (Elsevier, 2018)
Objectives To assess the outcomes and toxicity of first-line methotrexate (MTX) chemotherapy in low-risk postmolar gestational trophoblastic neoplasia (GTN) patients receiving 8-day methotrexate or one-day methotrexate infusion regimens. Methods This retrospective cohort study was conducted at the New England Trophoblastic Disease Center (NETDC), between 1974 and 2014, and included 325 patients with FIGO-defined low-risk postmolar GTN receiving first-line 8-day MTX/folinic acid (FA) or one-day MTX infusion and FA. Demographics, disease presentation, initial treatment plan, treatment outcome, and treatment-related adverse events were assessed. Results Sustained remission (84% vs 62%, p < 0.001) and need to switch to second-line therapy due to treatment-related adverse events (5.3% vs 0%, p = 0.001) were higher for 8-day MTX/FA compared to one-day MTX infusion. MTX resistance, however, was more frequent with one-day MTX (34.5%) than with 8-day MTX/FA (7.3%, p < 0.001). Relapse rates were similar with both regimens (3.0%). Compared to one-day MTX infusion, 8-day MTX/FA was associated with significantly higher gastrointestinal disorders (48% vs 24%), abnormal laboratory findings (48% vs 28%), eye disorders (37% vs 19%) and general disorders (22% vs 5%) (p < 0.001). Only infection frequency did not differ between 8-day MTX/FA and one-day MTX infusion (20% vs 12%, p = 0.083). Conclusions This is one of the largest studies to comprehensively catalogue toxicities associated with 8-day MTX/FA and one-day MTX infusion. Although treatment-related adverse events were more frequent with 8-day MTX/FA, these were all self-limited and resolved with no long-term sequelae. Given this and its higher effectiveness, 8-day MTX/FA remains the treatment of choice at NETDC for patients with low-risk postmolar GTN.
Keywords: Effectiveness; First-line methotrexate chemotherapy; Low-risk gestational trophoblastic neoplasia; Toxicity